2010
DOI: 10.3357/asem.2700.2010
|View full text |Cite
|
Sign up to set email alerts
|

ECG During Helicopter Underwater Escape Training

Abstract: The heart rate response to HUET habituates. HUET produces cardiac arrhythmias; these are asymptomatic and probably of little clinical significance in young, fit individuals. It remains to be seen if this is the case with either an older, less fit cohort of people or in those undertaking longer breath holds in colder water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Based on: Tipton (); Datta & Tipton (); Tipton et al . (); Shattock & Tipton (). * Predisposing factors include channelopathies, atherosclerosis, long QT syndrome, myocardial hypertrophy and ischaemic heart disease.…”
Section: Introduction: Historymentioning
confidence: 99%
“…Based on: Tipton (); Datta & Tipton (); Tipton et al . (); Shattock & Tipton (). * Predisposing factors include channelopathies, atherosclerosis, long QT syndrome, myocardial hypertrophy and ischaemic heart disease.…”
Section: Introduction: Historymentioning
confidence: 99%
“…Even so, partial correlation coefficient analysis demonstrated that fitness is more important; at the same % body fat, individuals with a higher VO 2max had a heightened metabolic response (20). In addition, individuals with high levels of aerobic fitness do appear to have an attenuated cold shock or cardiorespiratory response to cold water immersion (105) and a lower number of arrhythmias/dysrhythmias during helicopter underwater escape (238).…”
Section: Individual Differences and Tolerancementioning
confidence: 99%
“…Indeed, the study lacks a distinct control group to directly test the hypothesis that the anxiety rating and, therefore, the threat perception, is not naturally lower on secondary CWI in contrast to an initial CWI. However, this idea can be roundly rejected based on evidence from other studies that have examined the anxiety response over consecutive immersions ( 1 ) or examined the extent of the CSR across two CWIs ( 11 ). Indeed, it seems that an increased or unchanged anxiety rating is more likely in con secutive immersions accompanied by an increased or matched CSR ( 2 ).…”
Section: Discussionmentioning
confidence: 95%